Legal Protection for Warehouse Receipt Holders After The Enforcement of Government Regulation Number 29 of 2022 - Prasmanto, Liska Wahyu; Kusumo, Ayub Torry Satriyo (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Warehouse receipts in Indonesia are regulated in Law Number 9 of 2006 concerning the Warehouse Receipt System. In this law, the warehouse receipt system is an activity related to the issuance, transfer, guarantee and settlement of Warehouse receipt transactions. The purpose of this study is to determine the regulation of the Warehouse receipt system according to laws and regulations in Indonesia and to determine the legal protection for Warehouse receipt holders after the enactment of Government Regulation Number 29 of 2022. The method in this research is normative juridical. The results of this study are the Revocation of the role of Perum Jamkrindo as the implementing institution for warehouse receipt guarantors through PP No. 29 of 2022 has created significant legal uncertainty in the implementation of the Warehouse Receipt System (SRG) in Indonesia.